IMPLEMENTATION OF TOTAL QUALITY MANAGEMENT (TMQ) TO IMPROVE SERVICE QUALITY IN HOSPITALS - R. Tauifiq Nur Muftiyanto (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This literature research aims to analyze the effect of implementing Total Quality Management (TQM) on improving the quality of services in hospitals. This research method involved a systematic review of scientific journals, case studies, and academic publications related to TQM in the healthcare sector. Based on a critical analysis of various literature sources, this study concludes that TQM, as a management philosophy that focuses on continuous improvement and customer satisfaction, plays a crucial role in establishing and evaluating quality health service standards. Core elements such as data-based performance measurement, business process management, and systematic development of human resource quality are recognized as key drivers in improving hospital performance. This research also reveals that TQM success depends on top management commitment, employee involvement, and cohesive strategy implementation throughout the organization. Frequently encountered obstacles include organizational cultural resistance and the need for adequate employee training. The findings of this study indicate that hospitals that effectively implement TQM not only achieve higher quality of service but also create a progressive work environment, which ultimately contributes to patient satisfaction and the long-term success of the institution. Recommendations are offered to facilitate ongoing TQM implementation, including the development of integration frameworks and change management strategies. This study provides insights for healthcare practitioners as well as policy makers in their efforts to improve service standards in hospitals through the implementation of TQM practices.